Devising urban ecosystem-based adaptation (EbA) projects with developing nations: A case study of Port Vila, Vanuatu. (1st February 2020) - Pedersen Zari, Maibritt; Blaschke, Paul M.; Jackson, Bethanna; Komugabe-Dixson, Aimée; Livesey, Chris; Loubser, David I.; Martinez-Almoyna Gual, Carles; Maxwell, Deborah; Rastandeh, Amin; Renwick, James; Weaver, Sean; Archie, Kelli M.
Abstract: As the linked impacts of climate change and degradation of ecosystems continue to be felt, particularly in developing countries, it is vital that methods for development that concurrently address adaptation to climate change, rapid urbanisation, and ecosystem degradation be explored. Further development of approaches which are participatory and embedded in an understanding of the importance of symbiotic relationships between socio-cultural and ecological systems is particularly important. Ecosystem-based adaptation (EbA) is one such method that is gaining recognition and momentum in areas where developing nations face converging pressures and drivers of change. EbA methodologies to date, are often ill-defined in an urban context and lack consideration of future social and ecological scenarios however. In response, this paper describes a methodology for developing urban EbA projects in a small island developing nation context. The methodology was developed and applied by a multi-disciplinary team working under the auspices of the Secretariat of the Pacific Regional Environment Programme (SPREP). The application of this methodology in Port Vila, Vanuatu indicated: i) the needs of local people must be at the forefront of project planning, requiring a participatory design process; ii) EbA solutions development must be multidisciplinary and iterative; iii) appropriate quantitative and qualitative data is vital as a basis for EbA project development, requiring adequate time for data gathering; iv) urban and coastal EbA projects must be developed holistically, recognising socio-ecological systems that extend beyond the urban area itself; v) the complex overlapping landscape of governmental and international aid financed projects must inform the development of new EbA projects; vi) potential monetary and non-monetary benefits, costs and risks across multiple factors must be carefully assessed in EbA project development; and vii) project implementation requires ongoing engagement and a readiness to adapt to on-the-ground realities. Highlights: Local needs must be at the forefront of EbA project planning. EbA solutions development must be multidisciplinary and iterative. Quantitative and qualitative data is vital for EbA project development. Time is required for this data gathering. Urban EbA projects must recognise socio-ecological systems that extend beyond the urban area itself. Complex overlapping landscapes of adjacent projects must inform the development of new EbA projects.